Performance of sprinkler irrigation over surface methods of irrigation on growth and yield attributes of mustard - Singh, Pramendra; Chauhan, S. K.; Singh, S. K.; Goyal, V. (Annals of Agricultural Research, 2016)
A field experiment was conducted on sandy soil of Agricultural Research Station RAU, Bikaner during 2005-06 and 2006-07. The highest yield and yield attributes i.e. pods/plant, length of pod, seed/pod significantly increase up to the levels of 5 number of irrigation with operating the sprinkler for 3 hrs. The seed yield increased at 5 irri. × 3 hr. scheduled was 1540 kg/ha which is 63.13 and 31.39% greater than 3 irr. × 3 hr. and 4 irri. × 3 hr. treatment combination, respectively